(untitled) (مجلة البحوث الأكاديمية, 2022)
This papers aims to explore Libyan teachers’ opinions towards the use of needs analysis in an English language programme which is introduced at the Faculty of Arts in Misurata University, Libya. The participants in this study are 25 Libyan teachers who work at the Department of English at the Faculty of Arts, in Misurata. Their teaching experience of English range from three to more than ten years. The data for this study were collected by means of questionnaires which were distributed to the teachers and analyzed. The statistical data were analyzed by using Google Forms Application. The findings of the study revealed that Libyan teachers consider needs analysis as an important means in designing language programme course and learning materials. What is more, they reported that needs analysis can be conducted any time and it can provide Libyan teachers with a basis for the evaluation of an existing course.